Identity as Number: Reflections on Quantification, Gender, and Body (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This paper offers a critical examination of the dynamics of quantification that underpin identity classification processes in relation to gender, with a specific focus on the regulatory mechanisms governing the hormonal monitoring of professional trans and intersex athletes. These mechanisms illustrate how quantification translates complex social and biological phenomena into parameters that appear objective, yet simultaneously produce normative and performative effects. The apparent neutrality of such standards conceals, in fact, deeply political and value-laden choices that shape not only what the law recognizes as gender, but also the bodily characteristics deemed necessary to embody it.
Keywords: quantification; gender; indicators; fundamental rights; governance of bodies